Human Sigma: What, Why and Why Not (Journal of Organizational Psychology, 2017)
The high levels of employee disengagement at the global and national levels, pressures of the rising consumer empowerment, especially, on sales and service organizations, and growing need to ensure the delivery of high quality customer experience—all three, collectively, require a business solution to avoid their negative impact on the financial efficiency of organizations. Human Sigma, such a solution, is a philosophy as well as a strategy that focuses on strengthening the interactions of two most important Human system assets of a sales and service organization, namely, employees and customers. Accordingly, the nature and significance of Human Sigma are explained. A simplified alternative to Human Sigma— Net Promoter Score—is also suggested.
Keywords: Organizational Psychology; Human Sigma